PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN FPG INSURANCE - Umaternate, Abdul Rizal; Elmi, Farida (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The main issue in this study is the inneficiency of transformational leadership style which applied at FPG Insurance, it marked with the decreasing of the employee performance. This is thought to have been caused by low work discipline and bad work placement. This study is using qualitative research method with quantitative approach, the population is the whole employee of FPG Insurance which is 100 people, sampling method is using sensus with the sample as much 100 people. The method used in this study is a multiple regression analysis. It aims to examine the effect of three independent variables on a dependent variable. This method is used to get valid and reliable data, so it can be used to understand, solve and anticipate problems in the organization. transformational leadership style, work discipline and work placement together have significant effect on the employee performance in FPG Insurance. The conclusion is transformational leadership style, work discipline and work placement is empirically contributes to the employee performance results simultaneously and partially. Researcher recommend to the company to improve on transformational leadership style, work discipline, work placement and make a deeper research about employee performance